2015
DOI: 10.1111/jgh.13050
|View full text |Cite
|
Sign up to set email alerts
|

Never underestimate inflammatory bowel disease: High prevalence rates and confirmation of high incidence rates in Australia

Abstract: The burden of IBD in our local region is high. Demographic similarities allow these results to be applied to the broader Australian community. We propose that the number of existing and new cases each year in Australia has been previously underestimated. These revised figures will be important when planning the provision of health resources for these patients in the future and when assessing need for research funding priorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
4
45
3
Order By: Relevance
“…Crude IBD, CD, UC and IBDU 1‐year incidence rates in our study were also comparable with previous Australasian data. Data from Barwon in 2010–2011 report an incidence of 24.2, 14.7, 7.5 and 2.0 per 100 000 respectively . The 95% CIs for crude IBD incidence rates per 100 000 in the most recent Barwon data (18.9, 30.5) and our study (24.4, 33.7) overlapped, suggesting no significant difference in incidence across Australian regions.…”
Section: Discussionsupporting
confidence: 38%
See 2 more Smart Citations
“…Crude IBD, CD, UC and IBDU 1‐year incidence rates in our study were also comparable with previous Australasian data. Data from Barwon in 2010–2011 report an incidence of 24.2, 14.7, 7.5 and 2.0 per 100 000 respectively . The 95% CIs for crude IBD incidence rates per 100 000 in the most recent Barwon data (18.9, 30.5) and our study (24.4, 33.7) overlapped, suggesting no significant difference in incidence across Australian regions.…”
Section: Discussionsupporting
confidence: 38%
“…Prevalence rates of IBD in our study were comparable with previous Australasian data. Data from Barwon in 2010–2011 report similar crude 12‐month period prevalence rates for IBD, CD, UC and IBDU of 344.6, 197.3, 136 and 8.5 per 100 000 respectively . In Canterbury, crude point prevalence rates on 1 June 2005 were 308.2, 155.2, 145.0 and 8.0 per 100 000 respectively .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We also observed that disease presentation at diagnosis did not change significantly over the study period, which has been reported elsewhere [31]. However, an increase in the proportion of cases with L3 disease location over time was reported between 2007/2008 and 2010/2011 in the same area of neighbouring Australia, but the number of cases with complete disease location data was relatively small [24]. Nevertheless, this observation may be real, and although there is no clear explanation for this increase, investigation of the length of the small intestine has proven problematic and spurred the rapid evolution and introduction of methods for visualising the small intestine with minimal invasion.…”
Section: Discussionmentioning
confidence: 54%
“…In recent years, different studies from around the world have reported annual IBD incidence rates were increasing, plateauing or even decreasing [14,17,24]. While Asia-based population studies continue to show increasing IBD incidence rates, two recent Eastern Canadian studies found statistically significant reductions in IBD incidence among populations with previously high rates [11,13,14,25,26], whereas two separate Danish studies, conducted during a time period similar to that of our study, both observed increases in CD incidence and UC incidence in both men and women [27,28].…”
Section: Discussionmentioning
confidence: 99%